Reflective thinking and its relationship to Aspiration level on a sample of basic eighth students in Hama Governorate schools (Journal of Hama University, 2022)
The present study aimed at knowing the relationship between reflective thinking and aspiration level on a sample of Second Basic Education schools in Hama Governorate, and knowing the significance of differences among the members of the study sample in reflective thinking and aspiration level, which may be due to the school place variable (city/ rural).The study sample consists of (365) students: (173) male and female students from Hama city, and (192) male and female students from Hama rural. The study tools was a scale to measure the reflective thinking, preparation Almshhrawy (2010), and a scale to measure the aspiration level , preparation by the researcher.The most important findings of Search:There was a median degree in reflective thinking in a sample of Second Basic Education schools in Hama Governorate.There were correlation statistically positive significant between the scores of students on the scale of reflective thinking and scores on a scale of aspiration level.There were not differences between the mean scores of students on the scale of reflective thinking due to the school place variable.There were differences between the mean scores of students on the scale of aspiration level due to the school place variable favor for the students in the city.
Keywords: Reflective thinking, Aspiration level, Second Basic Education school, Hama Province.